Using the EU-SILC for policy simulation: Prospects, some limitations and suggestions - Francesco Figari; Horacio Levy; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2007)
We explore the prospects for using the EU-SILC as the underlying micro-database for policy simulation across the EU. In particular we consider the issues to be addressed, and the advantages arising, from building a database from the EUSILC for the EU tax-benefit model, EUROMOD. In order to identify the issues and illustrate their importance a trial database for Spain is constructed. It is used within EUROMOD to calculate some selected social indicators as well as indicators of work incentives and the effects of fiscal drag in Spain between 2003 and 2006. We conclude that, although transforming the EU-SILC into a database for EUROMOD would require a significant amount of effort, this is likely to be worthwhile because of the consequential improvements in comparability across countries, efficiency in developing and maintaining the model for many countries and simplification of access arrangements. We therefore offer some suggestions for how to improve the User Database for this purpose.
Keywords: C81; C88; I32; 330; EU-SILC; European Union; Microsimulation; Politische Entscheidung; Politische Willensbildung; Simulation; Computerunterstützung; EU-Staaten